A first-principles density functional theory study on the piezocatalytic activity of tetragonal perovskite PbTiO3 - Sun, Xinyi; Zhu, Xiangyu; Kan, Erjun; Zhan, Cheng (Frontiers in Physics, 2025)
Piezoelectric materials have been found to possess high catalytic activity under external mechanical excitations, such as ultrasonic waves or collisions. Energy band theory (EBT) based on electronic excitation in semiconductors has been widely used to investigate piezocatalytic activity from a macroscopic perspective, while the microscopic correlation between the piezoelectric feature and surface chemical reactivity was not fully understood at the current stage. In this work, to overcome the limitation of conventional finite element modeling of piezoelectric materials, we employ the first-principles density functional theory (DFT) to study the electronic properties, macroscopic electrostatic potential, surface polarization, and chemical adsorption energy of tetragonal PbTiO3 under external mechanical strains. The correlations between the band structure, piezopotential, space charge distribution, and surface adsorption energy of the *OH/H groups are discussed in our work. Our simulation shows that the bulk PTO and layered PTO exhibit opposite trends in the band gap change under external strain. In addition, a nonmonotonic correlation between the change of dipole moment piezopotential versus the applied strain was found in few-layer PTO, which could directly quantify the driving force of piezocatalysis. Finally, the enhanced surface adsorption of *OH and *H on PTO was observed under both tensile and compressive strain, which reveals how piezoelectric features affect the surface chemical process in thermodynamics. Our work provides a significant mechanistic insight into the piezocatalytic behavior of general polar perovskite, which could facilitate the development of piezoelectric materials in energy conversion and environmental applications.